Pesticide Residue Analysis of Fruit Tomato (Lycopersicon commune) and Vegetable Tomato (Lycopersicon Pyriporme) at Traditional Market of Makassar City 2014 - Nur, Nahda Ulmiati; Selomo, Makmur; Raodhah, Sitti (HIGIENE: Jurnal Kesehatan Lingkungan, 2015)
Pesticide residue is one of the supporting factors caused cancer in humans by contamination between toxic and food. Effects of pesticide residues are not happened directly to consumers, but in the long time, it can cause health problems, the monitoring of pesticide residues in food is one way to prevent cancer early that caused by toxic substances that contaminated fruits and vegetables, especially fruit tomato and vegetables tomato at traditional market of Makassar city. The purpose of the study is to determine the presence of pesticide residues of fruit and vegetable tomato in Makassar traditional markets and to determine the food safety of fruit and vegetabes tomato from pesticide residue in traditional markets of Makassar city 2014. This study used quantitative methods with a descriptive approach using field observations , interviews, sampling, and inspection of tomato samples. The sampling method was purposive sampling. Samples were taken from the most dominant distributor as a distributor of tomatoes at each sampling site. The results showed that all samples of fruit tomato and vegetable tomato at the traditional market of Makassar was not detected containig pesticide profenofos active residue detection limits based on gas chromatography instruments. Samples of fruit tomato at a traditional market and vegetable tomatoes in traditional B detected contain the active chlorpyrifos pesticide residues below the MRL of pesticides that are safe for consumption by the public and not detrimental to health for the active ingredient profenofos and chlorpyrifos, but it is possible there are other active ingredients or any other toxic substances contained in the tomato. Researchers suggest that; 1) To the office of the provincial agriculture should give socializing and training an ongoing basis and periodically to the farmers to pesticides in vegetables and fruits in accordance with the use and dosage .; 2) To the department of health and consumer organizations Indonesian foundations that would increase oversight of pesticide distribution and use of pesticides and to improve education regarding the appropriate use of pesticides with IPM programs. 3) To further researchers should conduct the analysis of pesticide residues in foodstuffs other examination or other pesticide active ingredients as well as conduct periodic research as research conducted by researchers who are not frequently. Keywords: Traditional Market, pesticide residu, and Tomato